Mycobacteria exploit nitric oxide‐induced transformation of macrophages into permissive giant cells. (2nd November 2017) - Gharun, Kourosh; Senges, Julia; Seidl, Maximilian; Lösslein, Anne; Kolter, Julia; Lohrmann, Florens; Fliegauf, Manfred; Elgizouli, Magdeldin; Vavra, Martina; Schachtrup, Kristina; Illert, Anna L; Gilleron, Martine; et al.
Abstract: Immunity to mycobacteria involves the formation of granulomas, characterized by a unique macrophage (MΦ) species, so‐called multinucleated giant cells (MGC). It remains unresolved whether MGC are beneficial to the host, that is, by prevention of bacterial spread, or whether they promote mycobacterial persistence. Here, we show that the prototypical antimycobacterial molecule nitric oxide (NO), which is produced by MGC in excessive amounts, is a double‐edged sword. Next to its antibacterial capacity, NO propagates the transformation of MΦ into MGC, which are relatively permissive for mycobacterial persistence. The mechanism underlying MGC formation involves NO‐induced DNA damage and impairment of p53 function. Moreover, MGC have an unsurpassed potential to engulf mycobacteria‐infected apoptotic cells, which adds a further burden to their antimycobacterial capacity. Accordingly, mycobacteria take paradoxical advantage of antimicrobial cellular efforts by driving effector MΦ into a permissive MGC state. Synopsis: Immunity to mycobacteria triggers granulomas, involving multinucleated giant cells (MGC) as a unique macrophage species. Dysregulation of the TLR‐induced antimicrobial molecule nitric oxide propagates their transformation by interfering with the DNA damage response. Nitric oxide (NO) drives the transformation of macrophages into MGC. The underlying mechanism involves NO‐induced DNA damage and p53 impairment. MGC show exceptional capacity to ingest apoptotic cells and are permissive for mycobacterial persistence. Abstract : Immunity to mycobacteria triggers granulomas, involving multinucleated giant cells as a unique macrophage species. Dysregulation of the TLR‐induced antimicrobial molecule nitric oxide propagates their transformation by interfering with the DNA damage response.